Analysis on the Knowledge about Oral Potentially Malignant Disorders of a Male Motorcycle Community in Indonesia - Ahmada, Rafdan Affan; Ramadhanti, Deananda Setio; Surboyo, Meircurius Dwi Condro; Parmadiati, Adiastuti Endah; Ernawati, Diah Savitri; Mahdani, Fatma Yasmin; Ayuningtyas, Nurina Febriyanti (Journal of Health and Allied Sciences NU, 2023)
Background Oral potentially malignant disorders (OPMDs) are a group of oral lesions or conditions with a higher risk of malignant transformation. OPMD affects 4.47% of people worldwide, with predilection in males. The high tendency of frequent tobacco smoking and alcohol consumption may lead the male motorcycle community to have a higher risk for developing OPMD and malignant transformation.Objectives This article determines the level of knowledge about OPMD within a male motorcycle community.Methods This study uses a survey research design that is a questionnaire-based and descriptive study. Data were obtained using a Google Form, and IBM SPSS was used for analysis. Simple random sampling is the sampling method applied. The total knowledge score is divided into three levels, low (0–4), moderate (5–9), and high (10–15).Results The questionnaire was finished by 60 people entirely. All respondents (100%) were men, and the majority (83.00%) was aged between 20 and 21. A total of 26 respondents (43.30%) had moderate knowledge levels, followed by 21 with high knowledge levels (35.0%), and 13 with low knowledge levels (21.70%).Conclusion The majority of the male motorcycle community (43.30%) has a moderate knowledge level regarding OPMD. This study indicates the need for educational measures to improve awareness regarding OPMD in a high-risk community.
Keywords: malignant transformation; alcohol use; tobacco use; level of knowledge